The separate and combined effects of monoamine oxidase A inhibition and nicotine on resting state EEG. (January 2016) - Smith, Dylan M; Fisher, Derek; Blier, Pierre; Ilivitsky, Vadim; Knott, Verner
While nicotine is often associated with the neuropsychological effects of tobacco smoke, the robust monoamine oxidase (MAO) inhibition observed in chronic smokers is also likely to play a role. Electroencephalographically-indexed alterations in baseline neural oscillations by nicotine have previously been reported in both smokers and non-smokers, however, little is known about the effects of MAO inhibition in combination with nicotine on resting state EEG. In a sample of 24 healthy non-smoking males, the effects of 6 mg nicotine gum, as well as MAO-A inhibition via 75 mg moclobemide, were investigated in separate and combined conditions over four separate test sessions. Drug effects were observed in the alpha2, beta2, and theta band frequencies. Nicotine increased alpha2 power, and moclobemide decreased beta2 power. Theta power was decreased most robustly by the combination of both drugs. Therefore, this study demonstrated that the nicotinic and MAO inhibiting properties of tobacco may differentially influence fast-wave oscillations (alpha2 and beta2 ), while acting in synergy to influence theta oscillations.